Analisa untuk Kerja Sistem Komunikasi Serat Optik - Wiwien HadiKurniawati; Sarita Yuniarti Hanum (Jurnal Ilmiah Dinamika Teknik, 2008)
Growth of telecommunications technolog in this time very fast. Consumer of telecommunications no only seeing sophisticated a communications system technologv but also consider efficiency aspects and effectiveness. Communications system which quickly and cheap represent primalacie choice. Communications optic libre system offer speed of data which is better to be compared to copper strand of metal system Communications optic fibre system use light for the process ofdelivery of data by using method reflection of perfection, This article will explain more circumstantial about process and structure work opticfìbre communications system.